2020
DOI: 10.1016/j.jocn.2020.08.012
|View full text |Cite
|
Sign up to set email alerts
|

A national survey on the impact of the COVID-19 pandemic upon burnout and career satisfaction among neurosurgery residents

Abstract: Highlights U.S. neurosurgery residents report moderate burnout during the COVID-19 pandemic. Neurosurgery residents report uncertainty about future healthcare reform & earnings. The COVID-19 pandemic may impair residents’ achievement of surgical milestones. Burnout is associated with altered rotation or vacation schedules and lower PGY. Career satisfaction is associated with delivery of neurosurgical patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 33 publications
(58 reference statements)
1
73
0
2
Order By: Relevance
“…Sixty-one studies reported on fear related to an infectious disease outbreak [ 29 – 31 , 35 37 , 43 , 46 , 53 , 55 , 61 , 64 , 72 , 74 , 78 83 , 85 – 87 , 94 , 95 , 99 , 100 , 107 – 109 , 115 , 117 , 119 , 123 , 128 , 131 , 132 , 134 , 142 , 146 , 147 , 155 – 173 ]. Most of the studies ( n = 52) reported physician’s fear of infecting themselves or their family.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sixty-one studies reported on fear related to an infectious disease outbreak [ 29 – 31 , 35 37 , 43 , 46 , 53 , 55 , 61 , 64 , 72 , 74 , 78 83 , 85 – 87 , 94 , 95 , 99 , 100 , 107 – 109 , 115 , 117 , 119 , 123 , 128 , 131 , 132 , 134 , 142 , 146 , 147 , 155 – 173 ]. Most of the studies ( n = 52) reported physician’s fear of infecting themselves or their family.…”
Section: Resultsmentioning
confidence: 99%
“…Physicians reported the importance of having social support from friends, family, colleagues, and professionals (e.g., counsellors) in 29 studies [ 28 , 30 , 39 , 43 , 44 , 48 , 56 , 58 , 67 , 72 , 78 , 83 , 91 , 99 , 102 , 106 , 115 , 119 , 131 , 150 , 155 , 163 , 172 , 192 , 202 – 205 ]. Several studies ( n = 29) described positive personal coping strategies such as maintaining a positive attitude and resilience [ 37 , 46 , 83 , 100 , 106 , 108 , 136 , 202 , 205 , 206 ], practicing self-care (e.g., physical activity, eating well, resting, engaging in activities they enjoy) [ 30 , 35 , 56 , 65 , 70 , 91 , 102 , 103 , 117 , 119 , 129 , 131 , 150 , 151 , 207 ], and engaging with religious practices [ 39 , 46 , 131 , 205 ] as a way to mitigate negative psychological outcomes. In contrast, two studies reported that physicians engaged in avoidance coping strategies (e.g., screaming, crying, denial, self-blame, disengaging, substance abuse, etc.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, for those who work in a clinical setting, several studies have shown that there is substantially higher stress for health care workers during the pandemic compared with before the pandemic. 5 , 6 , 7 , 8 , 9 , 10 These life changes are associated with serious concerns about the impact on the careers and well-being of faculty, staff, and trainees. Several recent studies 5 have examined the effects of burnout, stress, depression, and anxiety on frontline medical staff during the global pandemic.…”
Section: Introductionmentioning
confidence: 99%